Characterization of a Novel Gene, srpA, Conferring Resistance to Streptogramin A, Pleuromutilins, and Lincosamides in Streptococcus suis. (February 2022) - Zhang, Chaoyang; Liu, Lu; Zhang, Peng; Cui, Jingpo; Qin, Xiaoxia; Ma, Lichao; Han, Kun; Wang, Zhanhui; Wang, Shaolin; Ding, Shuangyang; Shen, Zhangqi
Abstract: Antimicrobial resistance is undoubtedly one of the greatest global health threats. The emergence of multidrug-resistant (MDR) Gram-positive pathogens, such as methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus faecium (VRE), and β -lactamase-resistant Streptococcus pneumonia, has severely limited our antibiotic arsenal. Numerous ribosome-targeting antibiotics, especially pleuromutilins, oxazolidinones, and streptogramins, are viewed as promising alternatives against aggressive MDR pathogens. In this study, we identified a new adenosine triphosphate (ATP)-binding cassete (ABC)-F family determinant, srpA, in Streptococcus suis ( S. suis ) by means of a comparative analysis of the whole-genome sequences of tiamulin (TIA)-resistant and TIA-sensitive bacteria. Functional cloning confirmed that the deduced gene can mediate cross-resistance to pleuromutilins, lincosamides, and streptogramin A in S. suis and S. aureus . A sequence alignment revealed that SrpA shares the highest amino acid identity with Vga(E) (36%) and shows canonical characteristics of ABC-F family members. In SrpA-ribosome docked compounds, the extended loop region of SrpA approaches the valnemulin-binding pocket in the ribosome peptidyl-transferase center and competes with bound valnemulin. A detailed mutational analysis of the loop residues confirmed that this domain is crucial for SrpA activity, as substitutions or truncations of this region affect the efficiency and specificity of antibiotic resistance. Intracellular antibiotics accumulation indicated that SrpA does not act as an efflux pump, while a ribosome binding assay supported the protective effects of SrpA on the ribosome by preventing antibiotic binding as well as displacing bound drugs. These findings clarify the mechanisms underlying resistance to ribosomal antibiotics.